Daily variation in the electrophysiological activity of mouse medial habenula neurones. (16th December 2013) - Sakhi, Kanwal; Belle, Mino D. C.; Gossan, Nicole; Delagrange, Philippe; Piggins, Hugh D.
<x xml:space="preserve">Abstract</x> Key points Neurones of the suprachiasmatic nucleus (SCN) contain a molecular clock that drives these cells to exhibit daily rhythms in electrical activity. The molecular clock may also be present in another brain structure, the medial habenula, and here we tested whether medial habenula neurones show daily changes in their electrical activity. Using a brain slice preparation in which the medial habenula is isolated from inputs from the SCN, we made recordings from mouse medial habenula neurones and determined that they exhibit daily variation in their electrical properties. By contrast, in mice lacking functional molecular clocks, medial habenula neurones did not show overt daily change in their electrical activity. These studies indicate for the first time that medial habenula neurones exhibit daily changes in electrical activity that require a functional molecular clock, but do not depend on signals from the SCN. Abstract Intrinsic daily or circadian rhythms arise through the outputs of the master circadian clock in the brain's suprachiasmatic nuclei (SCN) as well as circadian oscillators in other brain sites and peripheral tissues. SCN neurones contain an intracellular molecular clock that drives these neurones to exhibit pronounced day–night differences in their electrical properties. The epithalamic medial habenula (MHb) expresses clock genes, but little is known about the bioelectric properties of mouse MHb neurones and their potential circadian characteristics. Therefore, in this study we used a brain slice preparation containing the MHb to determine the basic electrical properties of mouse MHb neurones with whole‐cell patch clamp electrophysiology, and investigated whether these vary across the day–night cycle. MHb neurones (n = 230) showed heterogeneity in electrophysiological state, ranging from highly depolarised cells (∼ −25 to −30 mV) that are silent with no membrane activity or display depolarised low‐amplitude membrane oscillations, to neurones that were moderately hyperpolarised (∼40 mV) and spontaneously discharging action potentials. These electrical states were largely intrinsically regulated and were influenced by the activation of small‐conductance calcium‐activated potassium channels. When considered as one population, MHb neurones showed significant circadian variation in their spontaneous firing rate and resting membrane potential. However, in recordings of MHb neurones from mice lacking the core molecular circadian clock, these temporal differences in MHb activity were absent, indicating that circadian clock signals actively regulate the timing of MHb neuronal states. These observations add to the extracellularly recorded rhythms seen in other brain areas and establish that circadian mechanisms can influence the membrane properties of neurones in extra‐SCN sites. Collectively, the results of this study indicate that the MHb may function as an intrinsic secondary circadian oscillator in the brain, which can shape daily information flow in key brain processes, such as reward and addiction.